Investigation of the Mechanism Underlying Calcium Dobesilate-Mediated Improvement of Endothelial Dysfunction and Inflammation Caused by High Glucose - Zhou, Yijun; Qi, Chaojun; Li, Shu; Shao, Xinghua; Ni, Zhaohui (Mediators of Inflammation, 2019)
Background/Aims. Diabetic kidney disease (DKD) is a leading cause of end-stage renal disease. Calcium dobesilate (CaD) is widely used to treat diabetic retinopathy. Recent studies have demonstrated that CaD exerts protective effects against diabetic nephropathy. The aim of this study was to elucidate the molecular and cellular mechanisms underlying the protective effects of CaD. Methods. Human umbilical vein endothelial cells (HUVECs) were cultured with different D-glucose concentrations to determine the effects of high glucose on HUVEC gene expression. HUVECs were also incubated with CaD (25 μM, 50 μM, and 100 μM) for 3 days to determine the effects of CaD on HUVEC viability. db/db mice were treated with CaD. 2-[(Aminocarbonyl)amino]-5-(4-fluorophenyl)-3-thiophenecarboxamide (TPCA-1) blocked the nuclear factor-κB (NF-κB) pathway in HUVECs. A pentraxin 3 (PTX3) small interfering RNA (siRNA) intervention experiment was performed in the cells. An adenovirus-encapsulated PTX3 siRNA intervention experiment was performed in db/db mice. Western blot and real-time PCR analyses were used to detect PTX3, p-IKBa/IKBa (I-kappa-B-alpha), and p-eNOS/eNOS (endothelial nitric oxide synthase) expression in mice and HUVECs. Hematoxylin-eosin (HE) staining and periodic acid-Schiff (PAS) staining were used to observe renal tissue damage in mice. PTX3 expression was observed by immunohistochemical staining. Results. CaD downregulated the expression of PTX3 and p-IKBa/IKBa and upregulated the expression of p-eNOS/eNOS in vitro. When TPCA-1 was used, high glucose induced high PTX3 expression, and the expression of p-eNOS/eNOS increased. After PTX3 gene silencing, the expression of p-eNOS/eNOS also increased. In vivo, CaD reduced the expression of PTX3 and p-IKBa/IKBa in the kidneys of db/db mice and increased the expression of p-eNOS/eNOS. After PTX3 gene silencing, the urine protein and renal function of db/db mice were ameliorated, the glomerular extracellular matrix was decreased, and the expression of p-eNOS/eNOS was increased. Conclusions. Our results suggested that CaD may inhibit the expression of PTX3 by altering the IKK/IKB/NF-κB pathway, thereby improving endothelial dysfunction in HUVECs. PTX3 may be a potential therapeutic target for DKD.